Nutritional labeling: a review of its comprehensive approach to nutrition and health - Juan-Sebastián, Juan-Sebastián; Rojas Renjifo, Katerine; Ramírez-Guzmán, Sandra-Milena; Jaramillo López, Fressia (Revista Colombiana de Investigaciones Agroindustriales, 2024)
Nutritional labeling has gained significance in recent years due to increasing concerns about balanced diets and public health. Labeling regulations aim to ensure that consumers receive accurate and useful information to make informed decisions about their food choices. However, studies conducted in various countries have revealed frequent discrepancies between actual nutritional values and those declared on product labels. These inconsistencies are partly attributed to the lack of proper oversight by nutrition professionals. This article presents a review of scientific literature related to nutritional labeling, with the goal of proposing a standardized approach for its correct implementation. A bibliographic search was conducted in scientific databases using keywords related to the topic. Of the 596 articles initially identified, 101 relevant studies were selected based on inclusion and exclusion criteria. The results indicate that nutritional labeling can positively influence consumer purchasing decisions, provided it is accompanied by health and nutrition education. However, challenges persist in the general population’s ability to interpret this information. It is concluded that standardizing labeling and improving its application will help reduce errors and promote healthier eating habits, positively impacting public health.